ALIH KODE LAGU BERBAHASA JEPANG KE DALAM BAHASA INGGRIS - Rita Ratnasari; Charlina Charlina; Intan Suri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research discusses about code switching which are contained in One Ok Rock Song on the album of Jinsei x Kimi. The purpose of this research is to identify the types and forms from code switching contained in One Ok Rock Song on the album of Jinsei x Kimi. This research used qualitative research methods with listening and note-taking techniques. The data in this study amounted to twenty songs from the research conducted it was found that there are two types of code switching which is,eksternal code switching and internal code switching. For the form of code switching also found two forms which is code switching intersentential switching forms and intra sentential switching forms.Key Words: Code Switching, Album, Song